Framework for life cycle sustainability assessment of additive manufacturing - Ribeiro, Inês (2020)
Project FIBR3D (ref: POCI-01-0145-FEDER-016414) FCT grant (ref: UIDB/00667/2020 (UNIDEMI). Project KM3D (PTDC/EME-SIS/32232/2017).